Patrolling Strategy for Multiple UAVs with Recharging Stations in Unknown Environments - Vargas, Patrick; Kappel, Kristofer; Marins, João; Cabreira, Tauã; Ferreira, Paulo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
One of the primary concerns related to Unmanned Aerial Vehicles (UAV), especially multirotors, is the limited endurance to perform patrolling missions in large scale applications. The use of recharging stations spread throughout the area of interest is an alternative to prolong the total mission execution time. In such scenario, the UAV performs a coverage task and must return to one of the stations from time to time to recharge or replace the battery. In this paper, we propose a patrolling strategy for multiple UAVs with recharging stations in an unknown environment. The aerial vehicles should patrol the area using the NC-Drone algorithm while searching for a target. They build a matrix-based internal map to register visited places and the positions of the recharging stations. The UAVs are also able to exchange information among each other when they are within a communication range. During the patrolling, the aerial vehicles constantly monitor the energy spent and the remaining energy available in their batteries, according to a previously proposed energy model. We evaluate the proposed approach in three scenarios with different types of targets. The patrolling strategy was able to successfully perform the mission, detecting the targets and safely returning to the recharging stations multiple times. We were able to prolong the mission execution time, avoiding battery exhaustion and unexpected crashes